pengukuran Kinerja Pegawai Dengan Menggunakan Human Resource Scorecard (Studi Pada Kantor Pelayanan Kekayaan Negara dan Lelang Manado) - prasetya, Wahyu DWi (JURNAL RISET BISNIS DAN MANAJEMEN, 2016)
The purpose of this research is to identify the Key Performance Indicator (KPI) which represents human resource performance in KPKNL Manado. This research also ained to obtain the performance measurement result in KPKNL Manado using Human Resources Scorecard and to identify which of the KPIs have met given targetand which ones have failed. The research results showed that there are 17 KPIs that represents human resource performance in KPKNL Manado. Overally human resource performance in KPKNL Manado has successfully met given target as shown in all Human Resource Scorecard perspectitve. The result also indicated that there are 2 KPIs thet failed to meet target and the rest has succeed. Keywords: key performance indicator, human resource scorecard, financial perspective, customer perspective, internal process perspective, learning and growth perspective